Trade Liberalization and Development in ICT Sector and its impact on household welfare in Viet Nam - Tran Quoc Trung; Nguyen Tungm; Le Thuc Duc; Nguyen Cao Duc; Tran Hao Hung (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
The ICT sector in Viet Nam had not been developed until the 1980s. However, over the last decade of rapid growth, it has had a powerful impact on many aspects of life in this country. Although the ICT sector is still at an early stage of development and lags behind many other countries in the region, the government of Viet Nam made strong commitments to upgrade the nation's ICT capability and implemented significant reforms in terms of trade and investment liberalization in ICT sector over the last decade.
Keywords: F1; 330; Trade Liberalization; ICT; Household welfare; Viet Nam